2009
DOI: 10.1029/2008tc002387
|View full text |Cite
|
Sign up to set email alerts
|

Variable late Neogene exhumation of the central European Alps: Low‐temperature thermochronology from the Aar Massif, Switzerland, and the Lepontine Dome, Italy

Abstract: [1] Several recent studies proposed an important increase in exhumation rate in the western European Alps since circa 5-4 Ma. In order to assess potential spatial differences in exhumation histories, we present new apatite fission track (AFT) and apatite (U-Th)/He (AHe) ages from the central Aar Massif (Guttannen area, Switzerland) and the western Lepontine Dome (Formazza area, Italy). Internal U/Th zoning in apatites explains alpha-ejection-corrected AHe ages that are older than the corresponding AFT ages in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 86 publications
8
59
1
Order By: Relevance
“…Subsequent cooling rates to the present day are not well resolved in time but must have been slower, on average, with rates of ∼0.3 to 0.5 km Ma −1 . Vernon et al (2009b) obtained a similar result for the central Aar Massif. They also found evidence of rapid cooling, but earlier, with a rate of ∼1.0 km Ma −1 between 9 and 7 Mya as inferred from the elevation distribution of apatite fission-track ages.…”
Section: Thermochronometry and Exhumation Ratessupporting
confidence: 75%
See 3 more Smart Citations
“…Subsequent cooling rates to the present day are not well resolved in time but must have been slower, on average, with rates of ∼0.3 to 0.5 km Ma −1 . Vernon et al (2009b) obtained a similar result for the central Aar Massif. They also found evidence of rapid cooling, but earlier, with a rate of ∼1.0 km Ma −1 between 9 and 7 Mya as inferred from the elevation distribution of apatite fission-track ages.…”
Section: Thermochronometry and Exhumation Ratessupporting
confidence: 75%
“…measured, and even then, resolving such signals may depend on new techniques such as 4 He/ 3 He measurement in apatite (Shuster et al 2005). Some thermochronometry studies claim to have detected a signal, or at least to have found a better explanation for their data with a recent increase in relief , Vernon et al 2009b), but these studies have not demonstrated that an increase in relief is required to explain thermochronometric ages.…”
Section: Development Of High Reliefmentioning
confidence: 95%
See 2 more Smart Citations
“…U/Th and cosmogenic nuclide dating of cave deposits, however, revealed an increased valley incision since~0.9 Ma for this region (Haeuselmann et al, 2007). (2) Another promising site is the Reuss Valley in the NW Aar Massif, for which AHe data is already available (Vernon et al, 2009). Analytical complications (U-Th zoning of apatites), however, prevent a reliable estimation of palaeo-relief from that data.…”
Section: Predicting Most Promising Areas To Estimate Palaeo-reliefmentioning
confidence: 96%